Coal-fired power systems: oppportunities and challenges in the development of superalloys for boiler systems (2011)
Coal fired power systems are still integral part of energy generation in many countries. The fact that this scenario will remain for quite sometime has accentuated the pursuit of clean coal initiatives (CCPI) aimed at getting to near zero(NZE)the carbon emissions in coal power generation. One of the major challenges in development of clean coal technology is in the area of materials technology for the development of boiler/steam turbine and Integrated Gasification Combined Cycle (IGCC) systems. As the most critical component in the construction of boiler systems, the superheater tubes have to undergo the most severe service conditions and must meet Stringent requirements with respect to fireside coal-ash corrosion/erosion, steamside oxidation and spallation, along with creep strength, thermal fatigue strength, and weldability. This paper presents the challenges of developing novel superalloys for these systems and the methods being advanced to overcome the problems.